Konstitusionalitas Peradilan Adat dalam Penyelesaian Sengketa Masyarakat Adat di Kabupaten Tana Toraja - Marham, Usman; Husen, La Ode; Razak, Askari (Al-Ishlah: Jurnal Ilmiah Hukum, 2022)
This research encapsulates an attempt to thoroughly investigate and analyze the constitutionality of customary justice in the context of dispute resolution among indigenous peoples, with particular emphasis on the ways in which disputes are resolved through customary justice institutions in Tana Toraja Regency. The research method applied was a combination of a normative (doctrinal) legal research approach relating to legal theory and doctrine, and an empirical (non-doctrinal) legal research approach focusing on practical experience and field observations. The findings of this study underscore the importance of considering the political context of law in evaluating the constitutionality of customary justice, given that the system is faced with a range of complex challenges. In practice, the dispute resolution process through customary justice in Tana Toraja Regency is organized by a reconciliatory judge, who is tasked with facilitating the process of deliberation between the disputing parties with the aim of reaching a mutually acceptable agreement or decision. Recommendations from this study highlight the need for legislative efforts to formulate clearer laws and regulations regarding the role and procedures of customary justice in resolving disputes in indigenous communities. There is also a need for local policies that support the role of conciliatory judges in the customary justice system in Tana Toraja. This research not only provides a deeper understanding of customary justice practices, but also provides a foundation for improved policies and better legal practices in the future, which can strengthen the protection of indigenous peoples’ rights and support sustainable and inclusive development.